Hemidystonia as an Initial Manifestation of Leptomeningeal Metastasis - Hyun-Jung Jung (Journal of Movement Disorders, 2009)
A 76-year-old woman gradually developed action dystonia of the left hand and foot. Leptomeningeal metastasis of the right fronto-parietal area associated with gastric adenocarcinoma was found on the brain magnetic resonance imaging (MRI) and positron emission tomography (PET) studies. We discuss the mechanisms involved in the development of secondary hemidystonia and review dystonia associated with cortical lesions.